2011
DOI: 10.1111/j.1468-2370.2011.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Employee Well‐being and the HRM–Organizational Performance Relationship: A Review of Quantitative Studies

Abstract: There is a lack of consensus on the role of employee well‐being in the human resource management–organizational performance relationship. This review examines which of the competing perspectives –‘mutual gains’ or ‘conflicting outcomes’– is more appropriate for describing this role of employee well‐being. In addition, this review examines whether study attributes such as the measurement of key variables, the level of analysis and the study design affect a study's outcomes. The review covers 36 quantitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
668
4
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(744 citation statements)
references
References 70 publications
(263 reference statements)
21
668
4
11
Order By: Relevance
“…In addition, a vast amount of HPWP studies have reported positive effects on both employee-and organizational-level outcomes (see systematic review: Van De Voorde et al, 2012). Based on these reviews, it seems safe to say that transformational leadership and HPWP can be used together to achieve mutual gains for both employees and the organization.…”
Section: Mutual Gains For Employees and The Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a vast amount of HPWP studies have reported positive effects on both employee-and organizational-level outcomes (see systematic review: Van De Voorde et al, 2012). Based on these reviews, it seems safe to say that transformational leadership and HPWP can be used together to achieve mutual gains for both employees and the organization.…”
Section: Mutual Gains For Employees and The Organizationmentioning
confidence: 99%
“…Since its introduction in the mid-1990s, the HPWP framework has gained prominence as an innovative strategy for shaping positive employee attitudes and developing a more effective organization. HPWP are associated positively with employee well-being and organizational performance outcomes (Van De Voorde, Paauwe & Van Veldhoven, 2012). …”
Section: #11152mentioning
confidence: 99%
“…Firms need to create economic value through organisational effectiveness, but that has to be sustainable: 'good' HRM consists of policies and actions that work for the survival and success of firms in the long run, rather than just creating short-term returns to shareholders. HRM needs to contribute to long-term individual well-being, so where, for example, high performance work systems create strong financial returns but lead to stress and burnout, which have received more recent attention (van de Voorde, Paauwe, & Van Veldhoven, 2012), they cannot be counted as…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…The search was limited to scholarly articles and focused on studies which explored the impact of HR practices on attitudinal, behavioral intentions and behavioral outcomes. Although strategic HR scholars have increasingly explored the relationship between HR practices and well-being outcomes (Shantz, Arevshatian, Alfes, & Bailey, 2016;Van De Voorde, Paauwe, & Van Veldhoven, 2012) that focused on corporate volunteering, as the primary emphasis in those studies is not on non-profit organizations. We also omitted articles that focused on HR practices in a nonprofit context that were designed to benefit only paid employees or the public (i.e.…”
Section: Identification Of Studiesmentioning
confidence: 99%